2018
DOI: 10.1001/jamafacial.2017.1393
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3 Commercially Available Botulinum Toxin Neuromodulators on Facial Synkinesis

Abstract: IMPORTANCE Botulinum toxin neuromodulators are an important treatment for facial synkinesis. Whether a difference in efficacy exists among the 3 different botulinum neuromodulators used in treating this condition remains unknown.OBJECTIVE To evaluate the effectiveness of 3 commercially available botulinum toxin neuromodulators in the treatment of facial synkinesis. DESIGN, SETTING, AND PARTICIPANTSIn this single-blind, 3-arm comparison randomized clinical trial, 28 patients at the Facial Nerve Center, Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…We found that the dose ratio relationship between the two botulinum toxins was much more complex in the real world than was suggested by consensus panels [ 35 ] or meta-analyses of clinical trials [ 36 ], both of which concluded the botulinum toxins were equipotent and could be switched using a 1:1 conversion ratio. In this study, the incobotulinumtoxinA to onabotulinumtoxinA dose ratio was >1 across both conditions; there was considerable variability in the dose ratio and the inter-injection interval at an individual patient level, but mean dose ratios were all >1 and are consistent with the results of Kollowe and colleagues [ 18 ], Wilson [ 28 ], Thomas [ 29 ], and the preclinical studies cited above. Our results support that there is no fixed-dose ratio conversion between incobotulinumtoxinA and onabotulinumtoxinA, and consistent with the product label and recommendations from regulatory agencies, the potency units of onabotulinumtoxinA are not interchangeable with other botulinum toxin type A products [ 37 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the dose ratio relationship between the two botulinum toxins was much more complex in the real world than was suggested by consensus panels [ 35 ] or meta-analyses of clinical trials [ 36 ], both of which concluded the botulinum toxins were equipotent and could be switched using a 1:1 conversion ratio. In this study, the incobotulinumtoxinA to onabotulinumtoxinA dose ratio was >1 across both conditions; there was considerable variability in the dose ratio and the inter-injection interval at an individual patient level, but mean dose ratios were all >1 and are consistent with the results of Kollowe and colleagues [ 18 ], Wilson [ 28 ], Thomas [ 29 ], and the preclinical studies cited above. Our results support that there is no fixed-dose ratio conversion between incobotulinumtoxinA and onabotulinumtoxinA, and consistent with the product label and recommendations from regulatory agencies, the potency units of onabotulinumtoxinA are not interchangeable with other botulinum toxin type A products [ 37 ].…”
Section: Discussionsupporting
confidence: 89%
“…With respect to its potential to treat blepharospasm, studies suggest that onabotulinumtoxinA (20 U) and abobotulinumtoxinA (60 U) significantly outperform incobotulinumtoxinA (20 U) based on dynamic strain reduction after injection into the glabella [ 28 ], and sustained improvements in facial synkinesias at week 4 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies focusing on BTX-A treatment patterns and outcomes were included in this review. Seven prospective and two retrospective observational cohort studies comparing outcome measures before and after treatment and one randomized controlled clinical trial 2,4,5,7,8,10,12–15 . Details of these studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…There are several serotypes of botulinum toxin (A‐G), but only serotypes A and B are available commercially as abobotulinumtoxinA; incobotulinumtoxinA; onabotulinumtoxinA for serotype A, and rimabotulinumtoxinB for serotype B 4,5 . Many studies have been carried out in an attempt to show the superiority of one product against the other, referring to immunogenic potential, more localized spread after injection and duration of action as reasons for superiority, however, many of these studies are commercially driven and lack good randomization to definitively determine the best product 5‐8 . In contrast, studies have shown similarity in efficacy between the different preparations 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Many studies have been carried out in an attempt to show the superiority of one product against the other, referring to immunogenic potential, more localized spread after injection and duration of action as reasons for superiority, however, many of these studies are commercially driven and lack good randomization to definitively determine the best product. [5][6][7][8] In contrast, studies have shown similarity in efficacy between the different preparations. 9,10 Cost, however, is a driver for healthcare provision, nevertheless, there is a perception from patients that the cheaper the product, the poorer the efficacy.…”
Section: Introductionmentioning
confidence: 99%